Releituras de Celso Furtado: Brasil (2001-2012) - Ferreira, Jessé Gomes (2015)
Seeking to explain the causes leading to the developme nt and attempt to understand it, some economists were organized around central ideas, culminating therefore in the development of economic theories. The knowledge accumulated over the work by these scholars will make a significant contribution in shaping t he thinking of Celso Monteiro Furtado . Furtado developed numerous studies trying to understand the dynamics of underdeveloped structures, what their basic characteristics and the main factors responsible for the perpetuation of the status quo of these stru ctures. Starting from the question "What remains of underdevelopment characteristics in Brazil in the light of the thought of Celso Furtado?", This work is guided by the hypothesis that Brazil has not suffered between 2001 and 2012, significant structural changes that it could classifies it as a developed country. It has been for this work as a general objective to analyze the underdevelopment of elements that persist in Brazil in the light of the thought of Furtado. And as specific, characterize economic d evelopment, from the study of the classical schools, Marxist, neoclassical, Kaleckian, Keynesian and ECLAC of economic thought; describe the economic underdevelopment in light of Celso Furtado ideas; and, finally, evaluate from the particular epistemology of thought Furtado Brazilian economic reality, with emphasis on the analysis of underdevelopment elements. It was found that although there have been important advances in some sectors, the country maintains a significant structural heterogeneity. Hence th e relevance of Furtado's contribution to understanding the economic underdevelopment, because he is still a constant in our reality.